Impulsivity is longitudinally associated with healthy and unhealthy dietary patterns in individuals with overweight or obesity and metabolic syndrome within the framework of the PREDIMED-Plus trial - Carlos Gómez-Martínez; Nancy Babio; Jordi Júlvez; Stephanie K. Nishi; Fernando Fernández-Aranda; Miguel Ángel Martínez-González; Aida Cuenca-Royo; Rebeca Fernández; Susana Jiménez-Murcia; Rafael de la Torre; Xavier Pintó; Mirjam Bloemendaal; et al. (BMC, 2022)
Abstract Background Few studies have analyzed the associations between impulsivity and dietary patterns. Some of them have shown a cross-sectional inverse relationship between impulsivity and healthy diet scores, whereas others reported a positive association with unhealthy dietary assessments. We aimed to examine longitudinal associations of impulsivity trait with adherence to healthy and unhealthy dietary patterns in older participants at high risk of cardiovascular disease over 3 years of follow-up. Methods A 3-year prospective cohort analysis within the PREDIMED-Plus-Cognition study conducted in 4 PREDIMED-Plus study centers was performed. The PREDIMED-Plus study aimed to test the beneficial effect of a lifestyle intervention on the primary prevention of cardiovascular disease. The participants with overweight or obesity and metabolic syndrome included in the present study (n = 462; mean age of 65.3 years; 51.5% female) completed both the UPPS-P Impulsive Behavior Scale (range: 0-236 points) and the 143-item Food Frequency Questionnaire at baseline, 1-year and 3-years of follow-up. Ten diet scores assessing healthy and unhealthy dietary patterns were evaluated. Linear mixed models were performed adjusting by several confounders to study the longitudinal associations between impulsivity trait and adherence to dietary pattern scores over 3 years of follow-up (also assessing interactions by sex, age, and intervention group). Results Impulsivity were negatively associated with adherence to the Healthy Plant-Based [β = -0.92 (95%CI -1.67, -0.16)], Mediterranean [β = -0.43 (95%CI -0.79, -0.07)], Energy-Restricted Mediterranean [β = -0.76 (95%CI -1.16, -0.37)], Alternative Healthy Eating Index [β = -0.88 (95%CI -1.52, -0.23)], Portfolio [β = -0.57 (95%CI -0.91, -0.22)], and DASH [β = -0.50 (95%CI -0.79, -0.22)] diet scores over 3 years of follow-up, whereas impulsivity was positively related with adherence to the unhealthy Western diet [β = 1.59 (95%CI 0.59, 2.58)] over time. An interaction by intervention group was found, with those participants in the intervention group with high impulsivity levels having lower adherence to several healthy dietary patterns. Conclusions Heightened impulsivity was longitudinally associated with lower adherence to healthy dietary patterns and higher adherence to the Western diet over 3 years of follow-up. Furthermore, nutritional intervention programs should consider impulsivity as a relevant factor for the intervention success. Trial registration Name of registry: Effect of an energy-restricted Mediterranean diet, physical activity and behavioral intervention on the primary prevention of cardiovascular disease. Trial registration number: ISRCTN 89,898,870. Date of registration: 05/28/2014.